MASTER TRAINING IN ENGINEERING: RUSSIAN MODEL - Marina Yu. Prakhova; Svetlana V. Svetlakova (Высшее образование в России)
The article discusses the features of Master degree in engineering and technology, developed in the Russian model of Magistracy, and its differences from the Western model. There are analyzed the factors, which determine this diversity. The article also proposes measures, which permit to make an approach for master’s degree training closer to a traditional model.